3D Visualization of Geothermal System Structure Based on Inversion Model of Gravity Data. Case Study: Mt. Salak Region, West Java - Nanda Ridki Permana; Belista Gunawan (Al-Fiziya: Journal of Materials Science, Geophysics, Instrumentation and Theoretical Physics, 2023)
The geothermal power plant located in Gunung Salak plays a crucial role in increasing the electricity supply transmitted to the Java-Bali region, as the energy demand continues to rise. The objective of this research is to determine the 3D subsurface structure of Gunung Salak, specifically the distribution of the reservoir as the target for geothermal energy using the Gravity method. Gravity data, including gravity disturbance (gd), geoid, and Digital Elevation Model (DEM), were obtained from the ICGEM website with a total of 48740 data each. Based on the results of the residual anomaly map, the low anomalies beneath Gunung Salak have values from -5.15 to -1.88 mGal, which are suspected to be associated with the magma chamber. The high anomalies beneath the manifestations have values from 0.92 to 5.01 mGal, indicating andesitic basalt intrusive rocks believed to be the reservoir rock. Through the 3D inversion modeling of the subsurface structure of the Gunung Salak geothermal system, a clay cap with a density from 2.47 to 2.5 g/cc at depths of 0 to 700 m and andesitic basalt rock as the reservoir with a density from 2.74 to 2.91 g/cc at depths of 700 to 3000 m have been identified.